The Effect of Air Quality Parameter on Respiratory Diseases: A Systematic Literature Review - Wardono, Hari Rudijanto Indro; Susanti, R.; Wijayanti , Yuni; Cahyati, Widya Hary (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The issue of the air quality index and its impact on health, specifically human respiratory continues to be a global concern. Recent studies indicate that respiratory diseases are linked to the inflammation caused by air pollutants. The aim of this study was to review the correlation between air quality measurements and factors contributing to the rise in acute nasopharyngitis and other respiratory disorders. This study was a systematic literature review of English language articles published in peer-reviewed academic journals between January 1, 2018, and April 30, 2023. This study found that twelve eligible papers from five reputable electronic databases: PubMed, Springer, ScienceDirect, ProQuest, and Google Scholar were eligible included. Severe respiratory illnesses are caused by factors such as Particulate Matter (PM), nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO), ozone (O3), and air temperature. While all studies showed a direct association between these factors and respiratory diseases, the inconsistent association between O3 and AQI with respiratory disease may be attributed to differences in sample size and geographic settings. A comprehensive review study involving human subjects is necessary to validate these findings.